MORPHOFUNCTIONAL CHARACTERISTICS OF LEAVES AND FRUITS IN MALOIDEAE (ROSACEAE): b. THE ROLE OF SURFACE TISSUES IN THE FORMATION OF RESISTANCE TO FUNGAL DISEASES - T. Kh. Kumachova; O. O. Beloshapkina; A. S. Voronkov; A. S. Ryabchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Resistance to the effects of plant biotic stressors is determined by a set of factors. Among them, the leading protective role is often assigned to the physiological and biochemical characteristics of the surface tissues. However, one cannot ignore the specificity of the microstructural organization of the plant surface, since the nature of interactions in phytopathogenic organisms is more complex than the chemical impact. Meanwhile, the information accumulated to date about the structure of the surface tissues of the vegetative and reproductive organs of plants, and the interface of mycobiota, is fragmentary.Objective. Mature leaves and fruits taken from representatives of the subfamily Maloideae Werber (Malus domestica Borkh., Pyrus communis L., Cydonia oblonga Mill. and Mespilus germanica L.) were selected for the study.Materials and methods. Samples for the research were taken from the middle part of the crown of model trees in 3 replications. In recent years, scanning electron microscopy (SEM) with cryofixation is considered the most promising technique and is used to analyze the surface of biological organisms and identification of species. It is particularly informative in the case of organisms with complex surface micromorphology and for studying the biodiversity of pathogens. However, in this work we combined the methods of light, electron (SEM, TEM) and confocal microscopy. The samples were also studied using phytopathological and histochemical techniques. Condensed polyphenols were detected using K2Cr2O7 and FeCl3 as well as 4-(Dimethylamino)cinnamaldehyde (DMACA, Sigma-Aldrich).Results. On the basis of the obtained phytopathological materials and published data an overview of fungal diseases afflicting leaves and fruits of M. domestica, P. communis, C. oblonga and M. germanica was made. It has been established that a common feature of the Maloideae fruits is the accumulation of condensed polyphenols, which play an important protective role against biotic stressors, in the cells of the pericarp’s outer tissues. Anatomical and morphological characteristics of passive immunity, or horizontal resistance to fungal pathogens, include the specific nature of waxy and cuticular deposits, features of the formation of cuticular folds and peristomatic rings in the stomata area and microstrands at the base of trichomes, thickness of the cuticle and cork tissue, and the development of lenticels on fruits.Conclusion. The studied model plants suffer from a sufficiently wide range of diseases with different etiologies; among them, the most widespread and harmful are mycoses. In view of this, their resistance to fungal pathogens correlates with the specificity of the leaf and fruit surface microstructure and the content of phenolic substances (polyphenols) in the cells of the pericarp’s surface tissues.